Analysis on vibration of propeller with unilateral edge trimming based on parametric modeling - Yuebing YAO; Xin JIN; Jie LI; Junyun WU; Jiasheng LI (Zhongguo Jianchuan Yanjiu, 2022)
Objective In engineering, the edge trimming method is often used to solve the problem of ship-machine-propeller mismatch caused by excessive load. In order to explore the effects of edge trimming on the vibration characteristics of the propeller, this paper studies the vibration of a propeller with edge trimming based on parametric modeling. MethodsDTMB4381, DTMB4382 and DTMB4383 propellers are selected as research examples, then Matlab programming technology and the ANSYS secondary development program are combined to obtain the influence laws of different unilateral edge trimming on the vibration characteristics of the propeller, and the different reasons behind the corresponding influence laws are analyzed. ResultsFor the DTMB4381 propeller without skew, the natural frequency increases slightly with the increase of the edge trimming amount, but the mode shape does not change much. For the DTMB4382 and DTMB4383 propellers with skew, with the increase of the edge trimming amount, the change law of the natural frequency remains basically the same as that of the DTMB4381 propeller without skew. ConclusionsSkew does not change the vibration characteristics of a propeller under different unilateral trimming amounts; with the increase of the trimming amount, the natural frequency change rate of the two types of propeller shapes after chamfering will be significantly improved, and the increase is more pronounced at higher levels. The corresponding secondary development program can help the relevant personnel to select the optimal trimming scheme from the perspective of vibration characteristics in practical engineering, providing a theoretical basis and guidance for the design and improvement of trimming schemes.